Polycyclic aromatic hydrocarbons in permafrost peatlands - Pastukhov, Alexander G.; Loiko, Sergey V.; Kaverin, Dmitry K. (Scientific Reports, 2021)
The concentrations of 15 individual PAHs in 93 peat cores have been determined by using high-performance liquid chromatography methods. In the profile the qualitative and quantitative composition of PAHs was non-uniform estimated in a wide range: from 112 to 3673 ng/g with mean 1214 ± 794 ng/g. Among 15 identified individual PAHs, the main contribution to their total amount was made by heavy highly condensed PAHs in the Eastern European peat plateaus, in particular, 6-nuclear benzo[ghi]perylene (1021 ± 707 ng/g), whereas in West Siberian permafrost peatlands, light PAHs were dominating, mostly naphthalene and phenanthrene (211 ± 87 and 64 ± 25 ng/g, respectively). The grass-equisetum peat contained the maximum of heavy PAHs and the dwarf shrub-grass—the minimum. In grass-dwarf shrub, grass-moss and moss peat, the share of 2-nuclear PAHs was most significant: naphthalene and fluorene, as well as 6-nuclear benzo[ghi]perylene. The presence of benzo[ghi]perylene in the entire peat strata, including its permafrost layer, was a marker of the anaerobic conditions that persisted throughout the Holocene and they were necessary for the synthesis of this compound.